A method for preparing composite thermoelectric material based on regenerated nanocellulose
By regenerating composite materials of nanocellulose and SWCNT, combining TEMPO/NaBr/NaClO system dissociated cellulose and cold pressing technology, a composite aerogel film with microporous structure is formed, solving the flexibility and thermoelectricity of existing organic thermoelectric materials. The performance deficiency has achieved high thermoelectric performance and excellent mechanical properties of regenerated nanocellulose/SWCNT composite materials, suitable for self-energy supply of wearable electronic devices.
Patent Information
- Application Number
- CN202111348841.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-15
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-11-15
AI Technical Summary
Existing organic thermoelectric materials have shortcomings in maintaining flexibility and improving thermoelectric properties, and it is difficult to meet the self-energy needs of wearable electronic devices, especially in the case of vibration and bending deformation at different frequencies.
Using composite materials based on regenerated nanocellulose and SWCNT, a porous composite aerogel membrane is formed by preparing a mixture of nanocellulose aqueous solution and SWCNT suspension, and a porous composite aerogel membrane is formed by vacuum suction filtration and freeze-drying, and a microporous structure is formed by cold pressing. The cellulose is dissociated in combination with the TEMPO/NaBr/NaClO system to improve the material's conductivity, Seebeck coefficient and mechanical properties.
It has achieved high electrical conductivity, high Seebeck coefficient and low thermal conductivity composite materials, with excellent mechanical properties, meet the self-energy needs of wearable devices, and is simple in process and low in cost, suitable for large-scale industrial promotion.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of thermoelectric materials, and more specifically to a method for preparing a composite thermoelectric material based on regenerated nanocellulose. Background Art
[0002] In recent years, with the development of miniaturization and micro-miniaturization of wearable electronic devices, flexible organic thermoelectric materials have attracted more and more attention from researchers. Thermoelectric materials can directly convert the temperature difference between the body surface and the environment into electrical energy, thereby realizing self-powered wearable electronic devices and avoiding the trouble of repeated charging and frequent disassembly of traditional batteries.
[0003] At present, although a single organic thermoelectric material has low thermal conductivity, its PF value is low, and its thermoelectric performance needs to be further improved. In addition, because the application of wearable devices involves vibrations of different frequencies and bending deformation, the material is required to have a certain toughness and mechanical strength while maintaining flexibility. Therefore, the current organic thermoelectric materials are still difficult to meet the self-powered needs of wearable electronic devices. In recent years, people have found that through the combination of different materials, the performance advantages of different components can be integrated, and the synergistic effect achieved through structural regulation can show performance that a single material does not have.
[0004] As we all know, as early as 4000 years ago, humans have begun to use paper to record information. Entering the information age, paper has once again attracted the interest of researchers with its advantages of light weight, flexibility, repeated folding and abundant raw materials. It is regarded as a matrix material of organic functional materials with great development potential. In addition, most papers are composed of natural cellulose, which is the most common renewable resource with amphiphilic structure in nature. The raw materials are abundant and easy to obtain, with an annual output of about 7.5×1010 tons. On the other hand, due to the extensive use of paper in human society, a large amount of waste paper is generated every day. These waste papers need to be further recycled. Therefore, the research on paper as a matrix and composite with existing single organic thermoelectric materials is increasing. However, traditional cellulose paper has some disadvantages, such as large fiber diameter (20-40 μm), resulting in rough surface, low transparency, and slightly insufficient mechanical properties, which limits its application in the field of flexible organic thermoelectric materials. Therefore, it is still a challenging task to provide a cellulose@organic composite thermoelectric material with high electrical conductivity, high Seebeck coefficient, low thermal conductivity and excellent mechanical properties. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a composite thermoelectric material based on regenerated nanocellulose with higher electrical conductivity, higher Seebeck coefficient, lower thermal conductivity and better mechanical properties.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing a composite thermoelectric material based on regenerated nanocellulose, comprising:
[0007] 1) Preparation of nanocellulose aqueous solution:
[0008] a. Soaking paper in water to remove impurities, diluting with deionized water and dispersing the paper to obtain pulp;
[0009] b. Add TEMPO, NaBr and NaClO to the pulp and adjust the pH value with sodium hydroxide to make it alkaline;
[0010] c. Repeatedly centrifugally washing the solution obtained in step b to make the pH value of the solution neutral, thereby preparing a nanocellulose aqueous solution;
[0011] 2) Preparation of SWCNT suspension:
[0012] d. dispersing SWCNTs in ethanol solvent to obtain a SWCNT suspension;
[0013] 3) Preparation of regenerated nanocellulose / SWCNT composite aerogel membrane:
[0014] e. Mix the nanocellulose aqueous solution and the SWCNT suspension and prepare a hydrogel membrane by vacuum filtration;
[0015] f. freeze-drying the hydrogel film obtained in step e to obtain a porous regenerated nanocellulose / SWCNT composite aerogel film;
[0016] g. Cold-pressing the porous regenerated nanocellulose / SWCNT composite aerogel membrane to obtain a regenerated nanocellulose / SWCNT composite aerogel membrane with a microporous structure.
[0017] A further technical solution is as follows: in the step a, the concentration of the pulp is 0.1-10 wt%.
[0018] A further technical solution is as follows: in step a, the paper includes toilet paper, rice paper, A4 paper and discarded books and newspapers.
[0019] A further technical solution is as follows: in the step a, the diluted solution is dispersed by mechanical stirring, ball milling or ultrasonic dispersion.
[0020] The further technical solution is: in the step b, the weight of TEMPO is 1-2wt%, and the weight of NaBr is 10-15wt%.
[0021] The further technical scheme is as follows: in the step b, the pH value is adjusted to 10 with sodium hydroxide, and the concentration of the sodium hydroxide is 0.1-0.8 mol / L.
[0022] A further technical solution is as follows: in the step c, the nanocellulose obtained by repeated centrifugal washing is mixed with deionized water to prepare a nanocellulose aqueous solution, wherein the concentration of the nanocellulose aqueous solution is 0.1% to 5wt%.
[0023] The further technical scheme is as follows: in the step d, the concentration of the SWCNT suspension is 0.01% to 1wt%, and the SWCNT is dispersed in the ethanol solvent by mechanical stirring and ultrasonic treatment.
[0024] The further technical scheme is as follows: in the step f, during freeze drying, the freezing temperature is -50 to -80°C, and the freeze drying time is 4 to 24 hours.
[0025] The further technical solution is: in the step g, during the cold pressing treatment, the pressure is 1-100 MPa and the cold pressing time is 1-20 min.
[0026] Compared with the prior art, the preparation method of the present invention uses paper whose main component is natural cellulose as a raw material and a TEMPO / NaBr / NaClO system as a cellulose dissociating agent to prepare nanocellulose. The nanocellulose has the advantages of high aspect ratio, high mechanical properties, abundant raw materials and low cost. Then, the nanocellulose is mixed with SWCNT, and a regenerated nanocellulose / SWCNT composite aerogel membrane with a macroporous structure is prepared by suction filtration film forming and freeze drying technology. The material is densified by room temperature cold pressing technology, the macroporous structure is eliminated, and the multi-level microporous structure is retained, which can reduce the thermal conductivity. At the same time, the high electrical conductivity and high Seebeck coefficient of SWCNT are retained to obtain a regenerated nanocellulose / SWCNT composite aerogel membrane with high thermoelectric performance. It can be seen that the composite thermoelectric material based on regenerated nanocellulose prepared by the preparation method of the present invention can reduce the thermal conductivity without significantly reducing the electrical conductivity of the material through the regulation of the microporous structure, and has high electrical conductivity, high Seebeck coefficient, low thermal conductivity and excellent mechanical properties. The preparation process is also relatively simple and the cost is low. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to more clearly understand the objectives, technical solutions and advantages of the present invention, the present invention is further described below in conjunction with embodiments.
[0028] The present invention provides a method for preparing a composite thermoelectric material based on regenerated nanocellulose, comprising:
[0029] 1) Preparation of nanocellulose aqueous solution:
[0030] a. Soak paper in water to remove impurities, dilute with deionized water and disperse to obtain paper pulp.
[0031] In this step, the paper includes toilet paper, rice paper, A4 paper and discarded books and newspapers, etc., and its main component is natural vitamins; preferably, the paper can be cut into pieces and then soaked in water to shorten the soaking time, and the concentration of the pulp is 0.1-10wt%, preferably 1wt%. Specifically, in the present invention, the diluted solution can be dispersed by mechanical stirring, ball milling or ultrasonic dispersion.
[0032] b. Add TEMPO, NaBr and NaClO to the pulp and adjust the pH value with sodium hydroxide to make it alkaline.
[0033] In this step, after adding TEMPO, NaBr and NaClO, stirring can be performed at room temperature to fully mix. It can be understood that the amount of TEMPO, NaBr and NaClO is calculated based on the solid content in the pulp. In the present invention, the weight of TEMPO is 1-2wt%, the weight of NaBr is 10-15wt%, and the pH value is adjusted to 10 with sodium hydroxide. The concentration of sodium hydroxide is 0.1-0.8mol / L, preferably 0.5mol / L, and the weight of NaClO is such that the pH value of the solution is about 10.
[0034] c. Repeatedly centrifuge and wash the solution obtained in step b to make the pH value of the solution neutral, thereby preparing a nanocellulose aqueous solution.
[0035] In this step, the nanocellulose obtained by repeated centrifugal washing is mixed with deionized water to prepare a nanocellulose aqueous solution, wherein the concentration of the nanocellulose aqueous solution is 0.1% to 5wt%; preferably, the centrifugal washing is repeated after the solution obtained in step b is transparent and the pH value has no significant change.
[0036] 2) Preparation of SWCNT suspension:
[0037] d. Disperse SWCNTs in ethanol solvent to obtain SWCNT suspension.
[0038] In this step, the concentration of the SWCNT suspension is 0.01% to 1 wt%, and the SWCNT is dispersed in the ethanol solvent by mechanical stirring and ultrasonic treatment, that is, the SWCNT suspension is a suspension formed by fully mixing the SWCNT and ethanol after mechanical stirring and ultrasonic treatment.
[0039] 3) Preparation of regenerated nanocellulose / SWCNT composite aerogel membrane:
[0040] e. Mix the nanocellulose aqueous solution and the SWCNT suspension and prepare a hydrogel membrane by vacuum filtration.
[0041] f. freeze-drying the hydrogel film obtained in step e to obtain a porous regenerated nanocellulose / SWCNT composite aerogel film.
[0042] In this step, during freeze drying, the freezing temperature is -50 to -80°C, and the freeze drying time is 4 to 24 hours. In the present invention, the freezing temperature is preferably -70°C, and the drying time is preferably 12 hours.
[0043] g. Cold-pressing the porous regenerated nanocellulose / SWCNT composite aerogel membrane to obtain a regenerated nanocellulose / SWCNT composite aerogel membrane with a microporous structure.
[0044] In this step, during the cold pressing treatment, the pressure is 1 to 100 MPa and the cold pressing time is 1 to 20 minutes.
[0045] It can be understood that the steps in the method for preparing the composite thermoelectric material based on regenerated nanocellulose of the present invention can be adjusted, combined and deleted in sequence according to actual needs. For example, a SWCNT suspension can be prepared first, and then a nanocellulose aqueous solution can be prepared, or a nanocellulose aqueous solution can be prepared first, and then a SWCNT suspension can be prepared. It can be adjusted according to actual needs.
[0046] The preparation method of the composite thermoelectric material based on regenerated nanocellulose of the present invention is described below in conjunction with specific embodiments.
[0047] Example 1
[0048] (1) 2 g of waste rice paper was cut into pieces, impurities were washed off, and the pieces were soaked in 200 mL of water and stirred at room temperature for 4 h. Then, the pieces were treated with a homogenizer for 1 h to prepare pulp of a certain concentration;
[0049] (2) adding 0.032 g TEMPO, 0.2 g sodium bromide and 20 mL sodium hypochlorite, stirring at room temperature, and adding dropwise 0.5 mol / L sodium hydroxide aqueous solution to adjust the pH value so that the pH value is maintained at around 10;
[0050] (3) After the solution in step (2) becomes transparent and the pH value does not change significantly, centrifuge at 8000 rpm, remove the supernatant, and dilute the centrifugal precipitate with water. Repeat this process three times to separate and obtain a nanocellulose aqueous solution;
[0051] (4) adding 0.5 g of SWCNT powder into 100 mL of ethanol to obtain a SWCNT suspension of a certain concentration;
[0052] (5) taking 200 mL of the nanocellulose aqueous solution in step (3) and 50 mL of the SWCNT suspension (carbon tube suspension) in step (4), mixing them thoroughly, and preparing a hydrogel membrane by vacuum filtration;
[0053] (6) freeze-drying the hydrogel film obtained in step (5) at -70°C for 12 hours to obtain a porous regenerated nanocellulose / SWCNT composite aerogel film;
[0054] (7) The regenerated nanocellulose / SWCNT composite aerogel membrane in step (6) is cold-pressed at 20 MPa for 5 min at room temperature to obtain a regenerated nanocellulose / SWCNT composite aerogel membrane with a microporous structure.
[0055] As we all know, the evaluation index of the thermoelectric performance of materials is the dimensionless thermoelectric figure of merit ZT = S 2 σT / κ, where S, σ, T and κ are the Seebeck coefficient, electrical conductivity, absolute temperature and thermal conductivity of the material respectively. It can be seen that the material requires a large Seebeck coefficient, high electrical conductivity and low thermal conductivity to obtain excellent thermoelectric performance. For organic polymers and their composite materials, due to their low thermal conductivity, the power factor PF is often used. 2 σ is used to measure the quality of the thermoelectric performance of the material.
[0056] The thermoelectric properties of the regenerated nanocellulose / SWCNT composite aerogel membrane with microporous structure obtained according to the ratio of this embodiment are: conductivity is 763.8S cm -1 , the Seebeck coefficient is 54.3μVK -1 , and the thermal conductivity is less than 0.5Wm -1 K -1 .
[0057] Example 2
[0058] The method is the same as that of Example 1, except that the waste rice paper in step (1) of Example 1 is replaced by A4 paper. The conductivity of the regenerated nanocellulose / SWCNT composite aerogel membrane with a microporous structure finally obtained in this example is 532.3S cm -1 , the Seebeck coefficient is 50.7μVK -1 .
[0059] Example 3
[0060] The method is the same as that of Example 1, except that the 50 mL of SWCNT suspension (carbon tube suspension) in step (5) of Example 1 is changed to 20 mL. The conductivity of the regenerated nanocellulose / SWCNT composite aerogel membrane finally obtained in this example is 128.8 S cm -1, the Seebeck coefficient is 51.4μVK -1 .
[0061] Example 4
[0062] The method is the same as that of Example 1, except that the 20 MPa in step (7) of Example 1 is changed to 30 MPa. The conductivity of the regenerated nanocellulose / SWCNT composite aerogel membrane finally obtained in this example is 792.7 S cm -1 , the Seebeck coefficient is 51.2μVK -1 .
[0063] Example 5
[0064] The method is the same as that of Example 1, except that the cold pressing time in step (7) of Example 1 is changed from 5 min to 10 min. The conductivity of the regenerated nanocellulose / SWCNT composite aerogel membrane finally obtained in this example is 807.2 Scm -1 , the Seebeck coefficient is 51.8μVK -1 .
[0065] In summary, the preparation method of the present invention uses paper whose main component is natural cellulose as a raw material, uses SWCNT as a thermoelectric functional component, and combines freeze-drying technology with room temperature cold pressing technology to give the material a microporous structure. While reducing the thermal conductivity, the high electrical conductivity and high Seebeck coefficient from the carbon tube component are retained to obtain a regenerated nanocellulose / SWCNT composite material with high thermoelectric performance, that is, paper is used as a raw material, and a TEMPO / NaBr / NaClO system is used as a cellulose dissociator to prepare nanocellulose, which has the advantages of high aspect ratio, high mechanical properties, abundant raw materials and low cost. Then, it is mixed with SWCNT, and a regenerated nanocellulose / SWCNT composite aerogel membrane with a macroporous structure is prepared by suction filtration film formation and freeze-drying technology, and then a room temperature cold pressing technology is used to prepare a regenerated nanocellulose / SWCNT composite aerogel membrane with a macroporous structure. The method promotes the densification of the material, eliminates the macroporous structure, and retains the multi-level microporous structure. The microporous structure can reduce the thermal conductivity of the material through phonon scattering. Compared with the macroporous structure, these microporous structures have smaller pore sizes and will not significantly reduce the mechanical properties and electrical conductivity of the composite material. The high electrical conductivity and high Seebeck coefficient of SWCNT can be retained to obtain a regenerated nanocellulose / SWCNT composite aerogel membrane with high thermoelectric performance. It can be seen that the composite thermoelectric material based on regenerated nanocellulose prepared by the preparation method of the present invention can reduce the thermal conductivity without significantly reducing the electrical conductivity of the material through the regulation of the microporous structure. It has high electrical conductivity, high Seebeck coefficient, low thermal conductivity and excellent mechanical properties. The preparation process is also relatively simple, low-cost, and green and environmentally friendly, which is convenient for large-scale industrial promotion.
[0066] The above description is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Those skilled in the art can make various equivalent changes and improvements based on the above embodiments, and all equivalent changes or modifications made within the scope of the claims should fall within the protection scope of the present invention.
Claims
1. A method for preparing a composite thermoelectric material based on regenerated nanocellulose, characterized in that: include: 1) Preparation of nanocellulose aqueous solution: a. Soaking paper in water to remove impurities, diluting with deionized water and dispersing the paper to obtain pulp; b. Add TEMPO, NaBr and NaClO to the pulp and adjust the pH value with sodium hydroxide to make it alkaline; c. Repeatedly centrifugally washing the solution obtained in step b, and mixing the nanocellulose obtained by repeated centrifugation and washing with deionized water so that the pH value of the solution is neutral, thereby preparing a nanocellulose aqueous solution with a concentration of 0.1% to 5 wt%; 2) Preparation of SWCNT suspension: d. Dispersing SWCNT in ethanol solvent to obtain a SWCNT suspension with a concentration of 0.01% to 1 wt%; 3) Preparation of regenerated nanocellulose / SWCNT composite aerogel membrane: e. Mix the nanocellulose aqueous solution and the SWCNT suspension and prepare a hydrogel membrane by vacuum filtration; f. freeze-drying the hydrogel film obtained in step e to obtain a porous regenerated nanocellulose / SWCNT composite aerogel film; during freeze-drying, the freezing temperature is -50 to -80°C and the freeze-drying time is 4 to 24 hours; g. The porous regenerated nanocellulose / SWCNT composite aerogel membrane is subjected to cold pressing treatment to obtain a regenerated nanocellulose / SWCNT composite aerogel membrane with a microporous structure; during the cold pressing treatment, the pressure is 1-100 MPa and the cold pressing time is 1-20 min.
2. The method for preparing a composite thermoelectric material based on regenerated nanocellulose according to claim 1, characterized in that: In the step a, the concentration of the pulp is 0.1-10 wt %.
3. The method for preparing a composite thermoelectric material based on regenerated nanocellulose according to claim 1, characterized in that: In step a, the paper includes toilet paper, rice paper, A4 paper and discarded books and newspapers.
4. The method for preparing a composite thermoelectric material based on regenerated nanocellulose according to claim 1, characterized in that: In the step a, the diluted solution is dispersed by mechanical stirring, ball milling or ultrasonic dispersion.
5. The method for preparing a composite thermoelectric material based on regenerated nanocellulose according to claim 1, characterized in that: In the step b, the weight of TEMPO is 1-2 wt %, and the weight of NaBr is 10-15 wt %.
6. The method for preparing a composite thermoelectric material based on regenerated nanocellulose according to claim 1, characterized in that: In the step b, the pH value is adjusted to 10 with sodium hydroxide, and the concentration of the sodium hydroxide is 0.1-0.8 mol / L.
7. The method for preparing a composite thermoelectric material based on regenerated nanocellulose according to claim 1, characterized in that: In the step d, SWCNTs are dispersed in an ethanol solvent by mechanical stirring and ultrasonic treatment.
Citation Information
Patent Citations
Self-supported and flexible poly(3,4-ethylenedioxythiophene) (PEDOT) nanofiber / single-walled carbon nanotubes (SWCNTs) composite thermoelectric material thin film and preparation method thereof
CN107146842A
Preparation method for composite aerogel thermoelectric material
CN109301060A